Chemical Characteristics of Chicken Meat Coated with Chicken Feet Gelatin-Basil Leaf Extract Based on Cold Storage Duration - Hadi, Imron; Bulkaini, Bulkaini; Fahrullah, Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chicken meat constitutes a significant source of animal protein in the Indonesian diet; however, its perishable nature results in a decline in quality during storage. The objective of this study was to evaluate the chemical characteristics of chicken meat coated with gelatin-basil leaf extract during cold storage. The present study employed a randomized experiment, incorporating three distinct treatments and five replicates. The treatments comprised cold storage duration (0, 3, and 6 days). The results demonstrated a significant effect (p<0.01) on the pH value, moisture content, water-binding capacity, and L a b color of chicken meat coated with chicken foot gelatin-basil leaf extract. The utilization of gelatin-basil leaf extract coating has been demonstrated to retard the decline in pH and moisture content, thereby preserving the water-binding capacity of chicken meat. Despite the decline in pH and color over time, the efficacy of the coating in preserving the quality of chicken meat, particularly during the initial storage phase, was demonstrated. The gelatin-basil leaf extract coating has been shown to contribute significantly to the prolongation of the freshness of chicken meat by slowing down the acidification and oxidation processes.